2010
DOI: 10.1186/1472-6963-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of prescribing error during the hospital stay and prediction of pharmacist's alerts overriding: a prospective analysis

Abstract: BackgroundDrug prescribing errors are frequent in the hospital setting and pharmacists play an important role in detection of these errors. The objectives of this study are (1) to describe the drug prescribing errors rate during the patient's stay, (2) to find which characteristics for a prescribing error are the most predictive of their reproduction the next day despite pharmacist's alert (i.e. override the alert).MethodsWe prospectively collected all medication order lines and prescribing errors during 18 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
0
24
0
5
Order By: Relevance
“…However, initiatives such as e-prescribing for doctors are not yet in full use and one could argue that prescribers cannot rely solely upon such decision support aids. Doctors must still have a certain amount of background knowledge and recognition to be able to understand if an incorrect answer has been given and to know when to override an alert [2,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, initiatives such as e-prescribing for doctors are not yet in full use and one could argue that prescribers cannot rely solely upon such decision support aids. Doctors must still have a certain amount of background knowledge and recognition to be able to understand if an incorrect answer has been given and to know when to override an alert [2,36].…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom (UK), this is at the beginning of the 2 year Foundation Programme which immediately follows basic medical education.Prescribing is one of the biggest steps in practice in the transition from being a medical student to being a Foundation Year 1 (F1) doctor. From being unable to prescribe by law as medical students, new doctors have the responsibility for prescribing powerful,potentially high risk drugs [1].Often it is junior doctors who prescribe most drugs in hospital [2] and their ability to do this safely and effectively is a concern both in the UK [3] and internationally [4]. A number of previous studies have found that new doctors are not as well prepared for prescribing as they might be [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…New developments in information technology and the advent of electronic medical records with computerized physician order entry, ward-based clinical pharmacists, and standardized bar codes promise substantial reductions in the incidence of medication errors and adverse drug events. ED patients expect and deserve nothing less than the safest possible emergency medicine service 12 .…”
Section: Need Of Hospital Emergency Pharmacistmentioning
confidence: 99%
“…Il existe de nombreuses études concernant les problèmes médicamenteux détectés par les pharmaciens sur les prescriptions hospitalières [3,[5][6][7][8][9][10] et qui évaluent l'impact clinique [7][8][9] ou économique [10] mais de telles études spé-cifiques à l'activité de rétrocession n'ont pas été publiées en France. L'objectif de ce travail est de décrire, d'une part, les principaux problèmes médicamenteux détectés lors de l'analyse des prescriptions et, d'autre part, présenter les interventions pharmaceutiques formulées par les pharmaciens au sein de trois sites de rétrocession des HCL.…”
Section: Introductionunclassified